2021
DOI: 10.7717/peerj.11493
|View full text |Cite
|
Sign up to set email alerts
|

Short-chain soluble polyphosphate fertilizers increased soil P availability and mobility by reducing P fixation in two contrasting calcareous soils

Abstract: Short-chain polyphosphate fertilizers have been increasingly applied in agriculture, but little is known about the chemical behaviors of polyphosphate in soils. Herein, a cylinder experiment was carried out to investigate the influences of different P types (i.e., mono-ammonium phosphate (MAP), phosphoric acid (PA) and ammonium polyphosphate (poly-P)) and their application methods (single vs split) on the mobility and availability of P in soil through a column millimeter-scale slice cutting method; meanwhile a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Compared with orthophosphates, the application of ammonium tripolyphosphate, followed by ammonium polyphosphate and phosphoryl triamide, was evaluated on maize, and these were determined to be the most effective compounds in preventing damage [ 113 ]. Shah and Chu [ 115 ] reported that split repeated polyphosphate application was superior to the single application method in increasing P mobility and use efficiency. Also, when P fertilizer is applied in a single basal method, it is easily fixed because of the high P concentration in fertilization placement [ 116 ].…”
Section: Phosphorus Fertilizers Use Efficiencymentioning
confidence: 99%
“…Compared with orthophosphates, the application of ammonium tripolyphosphate, followed by ammonium polyphosphate and phosphoryl triamide, was evaluated on maize, and these were determined to be the most effective compounds in preventing damage [ 113 ]. Shah and Chu [ 115 ] reported that split repeated polyphosphate application was superior to the single application method in increasing P mobility and use efficiency. Also, when P fertilizer is applied in a single basal method, it is easily fixed because of the high P concentration in fertilization placement [ 116 ].…”
Section: Phosphorus Fertilizers Use Efficiencymentioning
confidence: 99%
“…The enriched Microlunatus positively correlated with the Ca 8 -P i fraction, but negatively correlated with the Ca 2 -P i , Al-P i and Fe-P i fractions in both maize and soybean rhizospheres (Figures 1B, 2B), suggesting that Microlunatus may be involved in transformation of Ca 2 -P i , Al-P i and Fe-P i fractions into the Ca 8 -P i fraction through the formation of polyphosphate by Microlunatus and the subsequent hydrolysis of polyphosphate to replenish Ca 2 -P i , Al-P i and Fe-P i pools. A previous study also showed that the application of polyphosphate fertilizers increased the NaOH-extracted soil P fraction as a result of the relatively high solubility of polyphosphate (Shah and Chu, 2021). Since all the selected representative strains of these taxa related to P cycling were obtained from Illumina MiSeq sequencing analysis, future investigations on the isolation of representative strains of these taxa to test their functions are needed.…”
Section: Bacteria Affecting Rhizospheric P Transformation Under Maize...mentioning
confidence: 99%
“…The chain length of polyphosphates, which is determined by the number of phosphate groups they contain, affects their solubility and hydrolysis rate. In recent years, polyphosphate‐based fertilizer application has been shown to increase soil available P (Gao et al, 2020; Kang et al, 2021; Shah & Chu, 2021; Yuan et al, 2022) and improve crop yield (Holloway et al, 2001; McBeath et al, 2005; Torres‐Dorante et al, 2006) compared with traditional granular orthophosphate fertilizers. However, other studies reported that polyphosphate fertilizers had no obvious advantage compared with orthophosphate fertilizers in increasing soil P availability and crop yield (Chien et al, 2011; Coetzee et al, 2016; Khasawneh et al, 1979; Ottman et al, 2006).…”
Section: Introductionmentioning
confidence: 99%